2017
DOI: 10.1002/slct.201701216
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dual‐Fluorescence Emission Sensor Based on Photo‐Induced Electron Transfer and Aggregation‐Induced Emission Enhancement for Detection of Water

Abstract: We have designed and developed a tetraphenylethen (TPE)‐anthracene‐(aminomethyl)phenylboronic acid ester (AminoMePhenylBPin) structure RN‐1 possessing PET (photo‐induced electron transfer) and AIEE (aggregation‐induced emission enhancement) characteristics as a fluorescent sensor for detection of water in organic solvents. It was found that the appearance of fluorescence band in the low water content region is attributed to the fluorescence emission originating from the anthracene skeleton due to the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It was proposed that 17 could act as a dual-fluorescence emission sensor for detecting water in organic solvents. 75 A new strategy to achieve single-component white emission was demonstrated by Mei, Su and co-workers by combining vibration-induced emission (VIE) and AIE. 59 VIE-active molecules can undergo an excited-state conformational transformation from an intrinsic bent shape to a planarized shape.…”
Section: Dual Prompt Photoluminescencementioning
confidence: 99%
“…It was proposed that 17 could act as a dual-fluorescence emission sensor for detecting water in organic solvents. 75 A new strategy to achieve single-component white emission was demonstrated by Mei, Su and co-workers by combining vibration-induced emission (VIE) and AIE. 59 VIE-active molecules can undergo an excited-state conformational transformation from an intrinsic bent shape to a planarized shape.…”
Section: Dual Prompt Photoluminescencementioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] Generally, in each system, there is a specic range of water concentration available for detection; AIE is observed in high water concentrations, 7,29,30 whereas other systems exhibit optical changes in a relatively low concentration range. In this context, a reasonable approach to incorporating two mechanisms into one sensor molecule has been developed to detect and determine water in organic solvent sensitively in a wide concentration range, including the combinations of ICT or PET and AIE, [32][33][34][35][36][37][38][39] two water-induced reactions, 40 and two ICT-related mechanisms, 41,42 with rare exceptions based on one mechanism. 23,[43][44][45][46][47][48][49] However, the pioneering systems still have several problems to be solved, such as the appearance of non-response ranges to variations in water content and the indiscernible small changes in the photoabsorption and uorescence spectra as well as by the naked eye.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Moreover, fluorescent sensors for water have the potential to be functional materials, which would allow the visualization as well as detection and quantification of moisture or water droplets on material surfaces, and have promise to be applied to environmental, biomedical, and quality control monitoring systems. [12][13][14][15][16][17][18] Indeed, various kinds of organic fluorescent sensors for the determination of the water content in solvents based on their intramolecular charge transfer (ICT), [19][20][21][22][23][24][25][26][27][28][29] excited state intramolecular proton transfer (ESIPT), [30][31][32][33] photoinduced electron transfer (PET) [34][35][36][37][38][39][40][41] or solvatofluorochromic properties [42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…1–11 Moreover, fluorescent sensors for water have the potential to be functional materials, which would allow the visualization as well as detection and quantification of moisture or water droplets on material surfaces, and have promise to be applied to environmental, biomedical, and quality control monitoring systems. 12–18 Indeed, various kinds of organic fluorescent sensors for the determination of the water content in solvents based on their intramolecular charge transfer (ICT), 19–29 excited state intramolecular proton transfer (ESIPT), 30–33 photo-induced electron transfer (PET) 34–41 or solvatofluorochromic properties 42–47 have been designed and developed. The effects of ICT, PET, and ESIPT on the fluorescent sensing properties for the detection of water were investigated based on the intermolecular interactions of the fluorescent sensors with water molecules, which demonstrated that ICT-, PET-, and ESIPT-based fluorescent sensors were suitable for the detection and quantification of a trace amount of water (below 1–10 wt% in almost every case) in solvents.…”
Section: Introductionmentioning
confidence: 99%